Relasi Kuasa, Demografi, dan Pernikahan Dini: Tinjauan Foucault pada Perempuan di Desa Beratwetan, Mojokerto - Rahmatia, Adinda Dhea; Harianto, Sugeng (Research Community for Critical Society and Environment, 2025)
This study aims to (1) describe the types abbreviations of slang language varieties on TikTok social media originating from the content of Bahasa Gaul Anak +62; (2) find out the abbreviation patterns from the data that has been found. The method used in this research is descriptive qualitative. The data source in this research comes from TikTok social media which highlights the use of abbreviations in the content of (Bahasa Gaul Anak +62) in the content and comments column. The data collection techniques used, namely (1) tapping techniques by means of screenshots and (2) reading and writing techniques. The steps of data analysis, namely (1) recording and collecting data in the form of slang abbreviations on TikTok social media which focuses on the content of the content called (Bahasa Gaul Anak +62) and the comments column; (2) analyzing the data obtained according to the variety of abbreviations formed; (3) determining the patterns created from the abbreviations that have been found; (4) describing and analyzing data according to the patterns that have been found; (5) concluding the results of the analysis. The results showed that there are three forms of abbreviations that focus on the content of the (Bahasa Gaul Anak +62) on TikTok social media, namely abbreviations in the form of initialisms, acronyms, and contractions. Abbreviations in the form of initialisms were found as much as (43) data with two word-forming patterns, abbreviations in the form of acronyms were found as much as (52) data with twelve word-forming patterns, and abbreviations in the form of contractions were found as much as (4) data with four word-forming patterns. The most domain type of abbreviations in Bahasa Gaul Anak +62 content is acronyms.